The feedback-related negativity reflects “more or less” prediction error in appetitive and aversive conditions - Huang, Yi; Yu, Rongjun (Frontiers in Neuroscience, 2014)
Humans make predictions and use feedback to update their subsequent predictions. The feedback-related negativity (FRN) has been found to be sensitive to negative feedback as well as negative prediction error, such that the FRN is larger for outcomes that are worse than expected. The present study examined prediction errors in both appetitive and aversive conditions. We found that the FRN was more negative for reward omission versus wins and for loss omission versus losses, suggesting that the FRN might classify outcomes in a “more-or-less than expected” fashion rather than in the “better-or-worse than expected” dimension. Our findings challenge the previous notion that the FRN only encodes negative feedback and ‘worse than expected’ negative prediction error.